The Wharf by the Docks: A Novel - Warden, Florence, 1857-1929 (Salt Lake City, UT : Project Gutenberg, 2005)
"The Wharf by the Docks: A Novel" by Florence Warden is a fictional work written in the late 19th century. The story unfolds in the quaint town of Canterbury and revolves around Mr. George Wedmore and his family, particularly the budding romance between his daughter Doreen and the young barrister Dudley Horne. The narrative hints at underlying tensions and secrets that impact their lives, focusing on themes of love, trust, and mental instability. At the start of the novel, we meet Mr. Wedmore, who expresses concerns about Dudley due to the troubling legacy of Dudley$1 (Bs father and perceived changes in Dudley$1 (Bs behavior. The opening scenes introduce a warm domestic setting at The Beeches, showcasing Doreen's bright spirit and desire to understand Dudley's recent distance. Tensions escalate as Mr. Wedmore decides to confront Dudley about his intentions toward Doreen, meanwhile, Doreen's affection for Dudley and her suspicions about his well-being grow. The atmosphere is thick with intrigue and foreshadowing as the story begins to explore the precarious balance between love and worry, painting a portrait of young romance influenced by familial expectations and past traumas. (This is an automatically generated summary.)s
Release date is 2005-06-19
Marilynda Fraser-Cunliffe, Mary Meehan, and the Project Gutenberg Online Distributed Proofreading Team (https://www.pgdp.net)
Keywords: Dime novels; Romantic suspense fiction